Direct ink writing of lightweight 3D structures from alkali-activated waste fiberglass and glass microsphere fillers - Abel W. Ourgessa; Ahmed Gamal Abd-Elsatar; Mokhtar Mahmoud; Hamada Elsayed; Jozef Kraxner; Dusan Galusek; Enrico Bernardo (Open Ceramics)
This study explores the upcycling of glass waste into sustainable materials using additive manufacturing. The direct ink writing technique was used to 3D print structures from waste fiberglass activated with 3 M or 5 M NaOH. All inks showed shear-thinning behavior after 3 h of mixing, ensuring good printability. Printed structure with 5 M NaOH achieved higher compressive strength (5.2 MPa). Incorporation of glass microsphere fillers, synthesized from waste soda-lime glass via flame synthesis, improved print quality and reduced density. The printed structures displayed good layer adhesion and defect-free morphology. Thermal treatment at 800 °C produced porous glass ceramics with a foaming effect. Low molarity and microsphere incorporation minimized foaming while preserving the 3D structure. Final products had porosities of 88–93 %, bulk densities of 0.17–0.3 g/cm³, and compressive strengths of 1.6–3.2 MPa, demonstrating their potential as lightweight, sustainable building materials.